Strategi Ustadz dalam Mengembangkan Self Esteem Santri di Pesantren - Moch. Ahsan; Junaidi Junaidi (Program Studi Bimbingan dan Konseling Islam, 2025)
This study aims to explore the strategies used by ustadz (Islamic teachers) to develop students' self-esteem at Pesantren Al-Ma’ruf Kediri, a character-based educational context that remains under-researched. This research employs a qualitative method with a case study approach. The findings reveal that the ustadz implement an integrative and holistic strategy, manifested through positive communication and specific affirmations, personalized responsibility assignments, and the creation of an inclusive learning environment. The foundation of this entire strategy is the building of emotional closeness and direct role modeling, which creates a